2020
DOI: 10.1186/s43055-020-00274-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-traumatic abdominal pain: assessment of diagnostic value of MDCT enterography in small bowel diseases—a retrospective study

Abstract: Background: Because of its unique anatomy, overlap of its loops, and its continuous peristaltic motion, imaging of the small bowel is a big challenge. Non-traumatic abdominal pain of small bowel origin includes a spectrum of medical and surgical conditions ranging from minor to life-threatening conditions. Accurate diagnosis of these diseases is essential to reduce morbidity and mortality. The aim of our study is to assess the role of MDCT enterography in evaluation and diagnosis of different small bowel cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In this study, small bowel neoplasm and inflammation were the most common SI pathology, which aligns with Paulsen et al and Shokralla et al, who demonstrated that SI inflammatory disorders are the most prevalent cause of bowel-related symptoms in adults, followed by neoplastic lesions in the elderly (4,6). Twenty-four patients (30%) were diagnosed with small bowel inflammatory disorders, 17 (70.9%) of which were proven laboratory and histopathologically to be due to IBD, and 7 cases (29.1%) were due to non-IBD causes including FMF, duodenitis, and nonspecific findings.…”
Section: Inflammationsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, small bowel neoplasm and inflammation were the most common SI pathology, which aligns with Paulsen et al and Shokralla et al, who demonstrated that SI inflammatory disorders are the most prevalent cause of bowel-related symptoms in adults, followed by neoplastic lesions in the elderly (4,6). Twenty-four patients (30%) were diagnosed with small bowel inflammatory disorders, 17 (70.9%) of which were proven laboratory and histopathologically to be due to IBD, and 7 cases (29.1%) were due to non-IBD causes including FMF, duodenitis, and nonspecific findings.…”
Section: Inflammationsupporting
confidence: 91%
“…Twenty-four patients (30%) were diagnosed with small bowel inflammatory disorders, 17 (70.9%) of which were proven laboratory and histopathologically to be due to IBD, and 7 cases (29.1%) were due to non-IBD causes including FMF, duodenitis, and nonspecific findings. Shokralla et al and Tochetto et al demonstrated that estimated CTE sensitivity to detect small bowel inflammation was approximately 90% using biopsy as the reference standard and increased if associated with clinical, laboratory data, and follow-up [4,13]. According to Roda et al [14], Crohn's disease most commonly manifests in patients younger than 30 years old, with a second peak between 60 and 79 years old, which aligns with the findings of this study, which found that 13 patients were under 30 years old and four patients were over 60 years old.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation